Development of novel distribution automation system (DAS) on customer side distribution system - Ahmed, Musse Mohamud; W.Lian, Soo (IEEE PES XPLORER, 2012)
This research work has been done in designing and developing a Novel Distribution Automation System (DAS) in an open loop customer side distribution system. The research has utilized an automation techniques in both hardware and software environment using a communication network and embedded controllers along with power meters which has utilized the possible best solution for the fault operation and control tasks remotely. All hardware and software components have been developed and integrated together. Data exchange mechanism has been developed between the host computer and the embedded controllers that function in two way data exchanges between the two. The remote hardware controllers such as remoter terminal units (RTUs) are enabled to the communication modules to operate the substation remotely. The metering equipment is used as real time data restoration tool and gathers the customer's consumption energy information. Thus a multipurpose power meter is used as hand of the electrical utility at the customer side. IsaGraf provides communication – GSM (Global system for Mobile Communications) function blocks such as SMS (Short Message Service) “operating functions “SMS_send”, “SMS_test”, “SMS_gets” and developed “SMS usage functions. These are functions are created for GSM based messaging system to communicate with the person in charge to operate the system at anytime and anywhere remotely. Fabrication testing has been done on real distribution system and the results are shown in this paper.